Organization of operational and strategic controlling in integrated accounting system - Kutsyk, Petro; Ostapyuk, Natalia (Technology audit and production reserves, 2017)
Controlling is one of the most effective tools of the enterprise management system in the context of neutralizing hazards, threats, risks and ensuring the economic security of the enterprise. The aim of the article is determination of the place, role and importance of controlling (in particular, strategic and operational) in the enterprise management system, including through the prism of research into the use of controlling tools in the context of its sub-spheres. In the process of research, general scientific methods and specific methods of economic analysis are applied. It has been established that the controlling procedures that are carried out to support the management of an enterprise must be carried out using a system of analytical tools, and a clear relationship between the tasks (sub-spheres) of controlling and the tools that provide their solutions should be established. Strategic controlling coordinates the functions of strategic planning, control and strategic information management system. The objective is ensuring the long-term successful operation of the enterprise. The task of strategic controlling is maintenance and support of a strategic plan for ensuring its viability. Operational controlling involves creating and maintaining the level of efficiency of the system achieving the current local objectives of the company, managing the efficiency of the enterprise. This kind of controlling has its own peculiarities in the controlling system: focused on operational (current) planning; is the basis for the success of strategic controlling and strategic planning. Controlling affects the course of economic processes, the effectiveness of the use of economic means and the introduction and maintenance of certain areas of activity, but the object of controlling management processes. As a result of the research, the author proposes a system that includes about 20 analytical tools, many of which are used in management accounting, management and marketing. Along with this, the system introduces tools developed by the author independently or those that represent a modification of existing tools for specific sub-spheres of controlling.